Relations between bedtime parenting behaviors and temperament across 14 cultures - Pham, Christie; Desmarais, Eric; Jones, Victoria; French, Brian F.; Wang, Zhengyan; Putnam, Samuel; Casalin, Sara; Linhares, Maria Beatriz Martins; Lecannelier, Felipe; Tuovinen, Soile; Heinonen, Kati; Raikkonen, Katri; et al. (Frontiers in Psychology, 2022)
Objectives: The present study examined parental sleep-supporting practices during toddlerhood in relation to temperament across 14 cultures. We hypothesized that passive sleep-supporting techniques (e.g., talking, cuddling), but not active techniques (e.g., walking, doing an activity together), would be associated with less challenging temperament profiles: higher Surgency (SUR) and Effortful Control (EC) and lower Negative Emotionality (NE), with fine-grained dimensions exhibiting relationships consistent with their overarching factors (e.g., parallel passive sleep-supporting approach effects for dimensions of NE). Methods: Caregivers (N = 841) across 14 cultures (M = 61 families per site) reported toddler (between 17 and 40 months of age; 52% male) temperament and sleep-supporting activities. Utilizing linear multilevel regression models and group-mean centering procedures, we assessed the role of between- and within-cultural variance in sleep-supporting practices in relation to temperament. Results: Both within- and between-culture differences in passive sleep-supporting techniques were associated with temperament attributes, (e.g., lower NE at the between-culture level; higher within-culture EC). For active techniques only within-culture effects were significant (e.g., demonstrating a positive association with NE). Adding sleep-supporting behaviors to the regression models accounted for significantly more between-culture temperament variance than child age and gender alone. Conclusions: Hypotheses were largely supported. Findings suggest parental sleep practices could be potential targets for interventions to mitigate risk posed by challenging temperament profiles (e.g., reducing active techniques that are associated with greater distress proneness and NE).